A strategic framework and toolbox for action research with small producers in value chains - Lone Riisgaard; Simon Bolwig; Frank Matose; Stefano Ponte; Andries du Toit; Niels Halberg (Danish Institute for International Studies (DIIS), 2008)
The paper presents a strategic and practical guide for how to design and implement action research in value chains in a way that integrates poverty, environmental and gender concerns. The focus is on small producers in developing countries and other weak chain actors such as small trading and processing firms. The toolbox guides the design and implementation of action research projects by presenting a step by step approach describing in detail (and with comprehensive checklists) what to do, questions to ask and issues to consider in each of the steps from the choice of overall research design, over participatory research and implementation of action, to evaluation, adjustment and exit. Reflections and decisions concerning effective action are assisted by a strategic framework for identifying 'upgrading' strategies potentially available for improving value chain participation for small producers, with the ultimate purpose of increasing the rewards and/or reducing the risks from participation. The stepwise approach is further aided by a comprehensive evaluation of specific action research methods, which first of all helps to select the specific research methods most suitable for the purpose and conditions of a particular action research project. A hypothetical example based on a real-world situation, shows how the toolbox might be applied in practice in its entirety, while real-world examples illustrate the most common upgrading strategies pursued by smallholders.
Keywords: 330; Wirtschaftsförderung; Klein- und Mittelunternehmen; Armutspolitik; Umweltauflage; Gleichberechtigung; Betriebliche Wertschöpfung; Projektbewertung; Entwicklungsländer